Reflections on delivering place-based climate risk data in support of local adaptation decisions - Adam J.P. Smith; Asher Minns; Robert J. Nicholls; Anna Beswick; Katie Jenkins; Sandy Avrutin; Craig Robson (Climate Risk Management)
Strengthening the adaptive capacity of the UK, via national plans and local-scale interventions, requires easy access to climate risk information and adaptation scenarios. Stakeholder engagement can ensure the right balance between top-down prescriptive modelling, and bottom-up, solution-focussed and lived experience approaches. National-scale, spatially-explicit, integrated climate risk frameworks can help inform the needs of localised climate risk assessments, but there are barriers to local actors accessing the information.